Pengaruh Kecanduan Telpon Pintar (Smartphone) pada Remaja (Literature Review) - Hidayanto, Dwi Kurnia; Rosid, Rosid; Nur Ajijah, Anisa Hasna; Khoerunnisa, Yulia (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM), Sekolah Tinggi Ilmu Sosial dan Ilmu Politik (STISIPOL) Candradimuka Palembang, 2021)
Smartphone is a popular technology among teenagers. The smartphone has a negative impact on teenagers, one of which is addiction. A smartphone addiction can interfere with activities in a youth's life. The purpose of this writing is to understand and customize the effects of the smartphone addiction. This writing was done using a qualitative descriptive method. The result of this writing is that excessive use of the smartphone can have a negative effect on teenagers. The potential effects of smartphone addiction include several aspects, including health, psychological aspects, academic, social aspects, and financial aspects.